Case Report: Presumed toxoplasmic optic neuritis - Williams, T.D. (Canadian Journal of Optometry, 2026)
Optic neuritis is regarded as a rather uncommon manifestation of toxoplasmosis. This repon concerns a patiem with suspected optic neuritis due to Toxoplasma gondii. (T. gondii).